2016
DOI: 10.1371/journal.pone.0163081
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leptomeningeal Metastasis by Contrast-Enhanced 3D T1-SPACE: Comparison with 2D FLAIR and Contrast-Enhanced 2D T1-Weighted Images

Abstract: IntroductionTo compare the diagnostic accuracy of contrast-enhanced 3D(dimensional) T1-weighted sampling perfection with application-optimized contrasts by using different flip angle evolutions (T1-SPACE), 2D fluid attenuated inversion recovery (FLAIR) images and 2D contrast-enhanced T1-weighted image in detection of leptomeningeal metastasis except for invasive procedures such as a CSF tapping.Materials and MethodsThree groups of patients were included retrospectively for 9 months (from 2013-04-01 to 2013-12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…11,25 In addition, a recent study comparing 2D-FLAIR, 2D-CE T1-weighted GRE, and black-blood imaging in the diagnosis of LC demonstrated that black-blood imaging showed a better detection rate of LC, regardless of the degree of the rater's experience. 26 Our study results were in good agreement with previous clinical studies, but our study differs from the previously published studies in some respects. First, we used clear inclusion criteria for those with LC and healthy patients.…”
Section: Discussionsupporting
confidence: 92%
“…11,25 In addition, a recent study comparing 2D-FLAIR, 2D-CE T1-weighted GRE, and black-blood imaging in the diagnosis of LC demonstrated that black-blood imaging showed a better detection rate of LC, regardless of the degree of the rater's experience. 26 Our study results were in good agreement with previous clinical studies, but our study differs from the previously published studies in some respects. First, we used clear inclusion criteria for those with LC and healthy patients.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, postcontrast FLAIR images may improve the detection of leptomeningeal metastases (Singh et al, 2000; Ercan et al, 2004; Hatzoglou et al, 2016). But in most cases volumetric contrast-enhanced sequences provide better sensitivity for leptomeningeal disease than two-dimensional T1-weighted or FLAIR images (Gil et al, 2016). …”
Section: Enhancing Detection Of Small Metastasesmentioning
confidence: 99%
“…The examination of CSF has critical value for the diagnosis of LMC (12). When cytologic analysis does not reveal LMC, LMC can be noninvasively diagnosed by neuroimaging alone in the appropriate clinical setting (4,6). The MR abnormalities included pial-arachnoid metastatic disease, metastatic disease coating the nerves, hydrocephalus, subependymal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as an invasive examination, CSF cytology is not proposed as a common examination (3,5). When cytologic analysis does not reveal LMC, LMC can be diagnosed by contrastenhanced (CE) magnetic resonance (MR) imaging alone (4,6). Leptomeningeal enhancement appears as a streakly pattern on MRI.…”
Section: Introductionmentioning
confidence: 99%